Thalidomide Chemotherapy-Induced Peripheral Neuropathy: Actual Status and New Perspectives with Thalidomide Analogues Derivatives - Cundari, Sante; Cavaletti, Guido (Mini Reviews in Medicinal Chemistry, 2009)
IMiDs compounds are a class of analogues of thalidomide, with greater immunomodulatory activity and a superior safety profile compared to the parent compound. They show substantial increase in potency and an interesting tolerability profile, primarily due to a decreased incidence of the most severe side effect of thalidomide, i.e. Chemotherapy- Induced Peripheral Neurotoxicity (CIPN). These novel aspects of the IMiDs compounds will be discussed.
Keywords: lenalidomide